2016
DOI: 10.2166/hydro.2016.078
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neural networks and neuro-fuzzy computing techniques for prediction of peak breach outflow

Abstract: Accurate prediction of peak outflows from breached embankment dams is a key parameter in dam risk assessment. In this study, efficient models were developed to predict peak breach outflows utilizing artificial neural network (ANN) and adaptive neuro-fuzzy inference system (ANFIS). Historical data from 93 embankment dam failures were used to train and evaluate the applicability of these models. Two scenarios were applied with each model by either considering the whole data set without classification or classify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Artificial Neural Networks (ANN) , are a form of computing inspired by the functioning of the brain and nervous system, and discussed in detail in a number of hydrologic papers [9]. The feed forward ANN has been adopted in many hydrological modeling studies because of its applicability to a variety of different problems [4].…”
Section: Study Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial Neural Networks (ANN) , are a form of computing inspired by the functioning of the brain and nervous system, and discussed in detail in a number of hydrologic papers [9]. The feed forward ANN has been adopted in many hydrological modeling studies because of its applicability to a variety of different problems [4].…”
Section: Study Methodologymentioning
confidence: 99%
“…The Levenberg-Marquardt (LM) training algorithm is a trust region based method with a hyper-spherical trust region [9]. This algorithm was implemented in this study using the Neural Network Toolbox of MATLAB, an example of Developed Structure of ANN with input combination as in Figure 4.…”
Section: Study Methodologymentioning
confidence: 99%
“…In addition, some scholars selected fuzzy mathematics to evaluate dam health state and the diagnosis techniques mainly consisted of fuzzy cluster analysis, fuzzy comprehensive evaluation, and fuzzy pattern recognition. 13,14 Wu et al 15 suggested an overall framework for the comprehensive evaluation of dam health adopting pattern recognition and fuzzy evaluation. On the basis of fuzzy control theory and expert experience, Ma et al 16 utilized fuzzy comprehensive evaluation method to assess the health state of concrete dams.…”
Section: Introductionmentioning
confidence: 99%